Stereochemistry and total synthesis of complex myxobacterial macrolides - Essig, Sebastian; Menche, Dirk (Pure and applied chemistry, 2013)
Polyketides are a very diverse family of natural products with an extremely broad range of biological activities and pharmacological properties, including antiproliferative, antibiotic, antifungal, or antiplasmodial activities, and in many cases specific targets are addressed at the molecular level. Their structures are characterized by diverse assemblies of methyl- and hydroxyl-bearing stereogenic centers enabling large numbers of stereochemical permutations, which are often embedded into macrolide rings. This complexity renders the stereochemical assignment and directed total synthesis challenging tasks. Within this review, we will detail practicable approaches for the stereochemical determination of diverse complex polyketides of myxobacterial origin by using computational and NMR methods in combination with novel procedures based on bioinformatics. Furthermore, we have developed efficient preparative strategies for the synthesis of these compounds, which have culminated in several first total syntheses. Key aspects of these various endeavors, which will also focus on the importance of conformational bias in complex polyketide analysis and synthesis, will be discussed within this review in the realm of the potent macrolide antibiotics etnangien and rhizopodin. Along these lines, we will also summarize novel methods for the rapid assembly of key structural elements of polyketides including a novel domino concept relying on a combination of a nucleophilic addition and a Tsuji-Trost reaction.
Gesehen am 17.02.2021